Evaluation of Limited Face-Face Pens Learning Readiness at State High School Level in Labuhanbatu District - Ruliansyah Putra Harahap; Nimrot Manalu; Samsuddin Siregar; Indra Kasih (Randwick International of Social Science Journal, 2023)
This study aims to determine the learning process of Limited Face-to-Face Physical Education at State Senior High Schools in Labuhanbatu Regency. In this study using a qualitative design where the research design is descriptive and tends to use analysis. Qualitative research is a research that is used to examine natural objects where the researcher is the key instrument, data collection techniques are carried out in a combined manner, data analysis is inductive, and the results of qualitative research emphasize meaning rather than generalization. The model in this study uses CIPP (Context, Input, Process, Product). The research sample from this study was physical education teachers at State Senior High Schools in Labuhanbatu Regency, totaling 15 people by means of total sampling. The data collection technique uses a questionnaire that has been prepared and given openly to physical education teachers. In the context evaluation aspect, a score of 80.1% was obtained in the very good category, in the input aspect, a score of 75.2% was obtained in the good category, in the process evaluation aspect, a score of 69.2% was obtained in the fairly good category, and on the product aspect a score of 74% was obtained in the good category. Based on the results of research that has been conducted on physical education teachers, the limited face-to-face physical education learning process conducted at the SMA level in Labuhanbatu Regency can generally be said to be good.